KAJIAN BAHAYA TANAH LONGSOR DAN UPAYA MITIGASI OLEH MASYARAKAT GUNUNGAPI TENGGER (Desa Ngadas, Kec. Poncokusumo, Kab. Malang Jawa Timur) - , EVI DWI LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The present study is focused on the issues linked to the risk management strategies in a touristic area exposed to landslides. This area is located in Ngadas Village, Poncokusumo, Malang, in which are located the two main touristic areas: The Bromo Crater and The Mount Semeru climbing/hiding site. The tourism activities developed in this region require an efficient access to these sites. Indeed, the area of Ngadas village is directly located on the scrap mountainside and only one main roadway is connecting the several areas of the Ngadas village. The quality of this network is very low because it is built on the steep slope existing along the main corridor. This location on the steep slope may directly cause landslides. This study aims to analyze: (1) the spatial distribution of the landslides by studying their occurrence and the impacts of the landforms on the landslidesâ occurrence in this precise area, (2) the impacts of landslide occurrence on socioeconomic issues for the Ngadas village (3) the mitigation strategies which have been done by the community and government to overcome the landslides in the studied area. The methodology used is a combination of a quantitative and a qualitative approach which consists in a study of the local strategies, a household survey by questionnaires and statistical analyses. This integrated approach allows us to have a precise knowledge of the socio-economic impacts and the current policies of the local government. The sampling frame used is a random sampling applied in each unit: the first one is the village, and the second one is the landform. The main results of the study show that (1) the spatial distributions of landslide events are concentrated at the top of the slopes of the Tengger volcano (2) the impact of landslides around the Ngadas corridor are economic and social, (3) the appropriate mitigation in this area is at the community level. Indeed our results indicate that the community of the Ngadas Village has a tradition that upholds respect to the village officials. This functioning may simplify the process of establising an efficient disaster strategy.